Development of phase fraction and flow rate meter in two-phase flows based on electrical impedance and pressure drop measurements - Wrasse, Aluísio do Nascimento (2019)
Multiphase flows are present in several areas of industry, such as in petroleum production in which oil, gas and water flow through pipelines. The knowledge of flow parameters – e.g. phase fractions, phase distribution and flow rate – is essential to monitor and control the processes where multiphase flow occur. Several measuring techniques have been developed and tested over the last years. Most of them cannot be applied universally but only in specific operation conditions requiring repeated calibration or adjustment procedures. Therefore, the development and improvement of measurement techniques applied in different operational conditions are of great importance. In this context, the main objective of this work is the development of an inline gas-liquid flow rate meter, non-radioactive, simple (to develop and install in the test facility) and presenting a high temporal resolution. The estimation of the flow rate of individual phases requires the measurement of volumetric fractions and velocities of the phases in a flow. Thus, different sensors have to be combined in a single device. Initially, we developed and evaluated a twin plane capacitive sensor to measure phase fraction in gas-liquid flows. The sensor is also capable of generating direct images of the flow, i.e., images of phase distribution can be generated without the use of reconstruction algorithms. Additionally, the twin geometry allows the estimation of the transit time of flow structures by cross-correlating signals of the twin sensors. We have evaluated the sensor in static and dynamic conditions by comparing the results with reference measurements and simulated values. A second system was proposed to estimate phase fractions and phase distribution in three-phase gas-liquid-liquid flows composed by a high conductive media (as commonly found in petroleum production with produced water). The system is based on a new topology of the well-established wire-mesh sensor. We performed measurements in static and dynamic conditions of stratified mixtures and of water-in-oil dispersions. Both impedance sensors can perform measurements at high acquisition rates. The twin-plane capacitive sensor has the advantage of being non-intrusive, whereas the novel wire-mesh sensor has a better spatial resolution. The last (and the main objective of this thesis) proposed system is a gas-liquid flow rate meter which combines information of the twin plane capacitive sensor and a Venturi meter. The flow rate of individual phases is calculated using data processing techniques and algebraic approximations. Here it is not required the previous knowledge of gas quality neither obtaining parameters from simulations or an extensive database – as commonly occurs in current commercial or prototype systems. The developed flow meter was tested in a horizontal flow loop for different combinations of gas and liquid flow rates. The main contributions of this work to the field of application is the development and combination of sensors, which allied to data processing techniques allows the estimation of flow parameters. The good results may encourage, in future works, the expansion of the flow rate meter to three-phase mixtures - by the aid of the new wire-mesh topology – and to industrial applications.